EFEKTIVITAS PROGRAM UPTD PPA KABUPATEN ROKAN HULU TERHADAP KORBAN KEKERASAN ANAK - Rinto Ari Siswoyo (Hirarki : Jurnal Ilmiah Manajemen dan Bisnis, 2024)
This research uses descriptive research with a qualitative approach. This research is limited by twothings, namely: (1) the effectiveness of the UPTD PPA program in Rokan Hulu Regency, (2)Supporting and inhibiting factors for the effectiveness of the UPTD PPA program in Rokan HuluRegency. The analysis used is data collection, data condensation, data presentation, and drawingconclusions. The results of this research indicate that the effectiveness of the UPTD PPA programin Rokan Hulu Regency is quite effective. Based on indicators of program effectiveness that isrunning quite well, namely the accuracy of program targets, program objectives and programmonitoring. However, the indicators for socialization of the UPTD PPA program have not beeneffective because many people still do not know about the UPTD PPA program. The supportingfactor for UPTD PPA is support from the central government and regional governments in the formof DAK and APBD funds. The inhibiting factor for UPTD PPA is that human resources areconsidered inadequate in terms of both employees and personnel due to employee transfers.UPTD PPA experts such as psychologists and legal consultants are also not yet available. In termsof facilities and infrastructure, there are no protection cars and motorbikes provided by thegovernment for outreach to victims